A human-inspired object handover controller. (July 2013) - Chan, Wesley P; Parker, Chris AC; Van der Loos, HF Machiel; Croft, Elizabeth A
In this paper, we present a novel controller for safe, efficient, and intuitive robot-to-human object handovers and a set of experiments to evaluate user responses to the robot's handover behavior. The controller enables a robot to mimic human behavior by actively regulating the applied grip force according to the measured load force during a handover. We provide an implementation of the controller on a Willow Garage PR2 robot, demonstrating the feasibility of realizing our design on robots with basic sensor/actuator capabilities. A user study comparing four variations of our controller shows that our design yields both human-like and human-preferred object handovers.